The Relationship Between Stress Levels With The Incidence Of Hypertension In The Elderly At Budi Agung Social Institution, Kupang City - Thamara Novelia Laly; dr. I Made Artawan M.Biomed., Sp.An-TI; dr. Derri Riskiyanti Tallo Manafe M.Sc (Cendana Medical Journal, 2025)
Background : Hypertension is called the "silent killer" and the leading cause of premature death worldwide. Hypertension causes high morbidity and mortality. Stress is one of the triggering factors for hypertension due to the activity of the sympathetic nervous system which results in an intermittent rise in blood pressure. Objective : This study aims to determine the relationship between stress levels and the incidence of hypertension in the elderly at the Budi Agung Social Institution, Kupang City. Method : This study is an analytic observational study using a cross-sectional design. The research population is the elderly at the Budi Agung Social Institution, Kupang City. Sampling using probability sampling technique and obtained as many as 40 research respondents. Stress levels were measured using a questionnaire DASS (Depression Anxiety Stress Scale) 14. Blood pressure was measured using a sphygmomanometer. Result : There are 15 respondents (37.5%) experiencing severe stress levels, as many as 13 respondents (32.5%) experiencing moderate stress, as many as 10 respondents (25.0%) experiencing mild stress, and as many as 2 respondents (5.0%) classified as not stressed or normal. In hypertension, there were 24 respondents (60.0%) with stage 2 hypertension, 12 respondents (30.0%) with stage 1 hypertension, 4 (10.0%) respondents with prehypertension, and none of the respondents had normal blood pressure or no hypertension. The results of the bivariate analysis using the spearmen rank test obtained p=0.001 (r=0.494). Conclutions : There is a relationship between stress levels and the incidence of hypertension in the elderly at the Budi Agung Social Institution, Kupang City Keywords : Stress Levels, Hypertension, Elderly, Budi Agung Social Institution, Kupang City